Collaborative governance of municipal solid waste in urban agglomerations: The case of Yangtze River Delta - Zhang, Jingru; Zhu, Mengyuan (Frontiers in Environmental Science, 2022)
As the by-product of modern life, the accelerating amount of municipal solid waste remains a wicked environmental and social problem that burdens megacities or populated cities in large. Apart from enhancing dexterity and proficiency in the intracity handling of waste, efficient and effective management needs to go beyond administrative boundaries and seek regional cooperation. Previous studies featuring Chinese regional waste management have paid scant attention to such endeavors. A SWOT analysis of the strengths and weaknesses of provinces and municipalities within the Yangtze River Delta, one of the country's top urban agglomerations, justifies the opportunities for further intra-region collaboration. This research analyzed the status quo of waste management in the region and laid out the enabling institutions, challenges, and policy suggestions for enhanced collaborations.